The Spatial Pattern of KIBS and their Relations with the Territorial Development in Romania - Zoltán Bujdosó; János Pénzes; Lóránt Dávid; Szilárd Madaras (Amfiteatru Economic Journal, 2016)
The development of Knowledge Intensive Business Services (KIBS) in recent decades can be interpreted as one of the major factors in a transition from an industrial economy into a knowledge-based one. It is an increasingly common belief that KIBS not only perform innovation activities in the service of the manufacturing sector, but they are also bridges of knowledge or innovation bridges, connecting the manufacturing sector, science and customers. The research questions were numerous. This paper attempts to reveal the existence of any relationship indicators, with special regards to the tourism indices and the KIBS related variables and how their position among different development indicators can be determined. It also explores whether there is any territorial difference or disparity within the counties of Romania. The results show that the KIBS related activities represent significant spatial concentration in the urban centres, especially in Bucharest. The concentration of KIBS-related local units were significant in several Romanian counties: Bra?ov, Cluj, Constan?a, Ilfov, Sibiu and Timi? (these counties and Bucharest contain almost 60 percent of the KIBS-related local units in Romania in 2013) and this territorial pattern is completely overlapped by the results of the multivariate cluster analysis. Different factors of KIBS are analysed by factor analysis, setting the KIBS-related indicator into the first component named 'Economic prosperity' with different development and infrastructural indicators. The research also reveals a strong correlation among the development indicators that predicts the significant spatial disparities from the respect of KIBS. The method used and the results produced could be useful for experts and decision makers in the field of economics and regional development.
Keywords: R1; 330; KIBS; economic development; Romania; factor analysis; cluster analysis; regional development